The selfie project: A successful approach to lifestyle monitoring and health promotion in adolescents - Mosconi , Giansanto; Feder, Simone; Albertin, Ilaria; Esposito, Marcello; Polgatti, Anna; Taverna, Franco; Turcinovich, Diego; Vecchi, Tomaso; Odone, Anna (Acta Biomedica Atenei Parmensis, 2023)
Adolescence is a critical period for the physical and cognitive development. To promote adolescents’ health and well-being, prevention and health education interventions are to be implemented at all levels of society, with schools and families playing a fundamental role. In 2015, the "Semi di Melo" Center for Education and Research on Childhood and Adolescence was established in Milan, northern Italy to help parents and teachers to better explicate their supportive role toward their children/students during adolescence. Through a survey called ’Selfie’, conducted via an internet-based, self-administered, and fully anonymous questionnaire, Semi di Melo collects qualitative and quantitative information on the demographic characteristics, lifestyle, leisure time, risk behavior, social relationships and mental wellbeing of middle and high school students in Italy. Data are then analyzed, interpreted, and shared with teachers, parents, and students during guided workshops and focus groups aimed at raising awareness of risky behaviours during adolescence and facilitating intergenerational exchange. To date, the Selfie questionnaire has been distributed to more than 400 Italian public schools, reaching more than 90,000 students. In late 2022, Semi di Melo and the University of Pavia started a collaboration to expand research on data acquired from the Selfie questionnaire through an analytical approach, allowing a more comprehensive understanding of Italian adolescents’ lifestyle, social, and psychological well-being. The gathered evidence will be made available to help educators, health and social care professionals, as well as local authorities and decision-makers to develop effective support systems and evidence-based interventions that help adolescents realise their full potential.